Investigation of metabolic effects of polymer nanomedicines using advanced metabolomics methods - AbuHammad, Ala (2024)
Breast cancer is the leading cause of death among women and the most frequently diagnosed female cancer worldwide, owing to its complex and heterogenous nature. Despite the intensified research that has been devoted to identifying the best treatment modalities for breast cancer, the mortality rate is still high due to frequent chemoresistance resulting in relapses and tumour metastasis. It is well known that chemoresistance, which is the failure of tumour cells to respond to chemotherapy, is the main challenge for any successful cancer treatment, and is not yet fully understood, since it originates from impairment of several biochemical pathways. In order to improve chemotherapies for breast cancer, intensive research showed promising results for nanomedicine applications. In particular, there is a focus on polymer nanoparticles for improving the therapeutic efficacy of the conventional chemotherapeutic agents for breast cancer. There is also an increasing attention towards the utilisation of natural products such as thymoquinone (THY), in combination-therapies with other chemotherapeutics agents, and is considered as a promising approach for enhancing the therapeutic efficacy of the conventional chemotherapies, by evading chemoresistance and reducing related severe side effects. At the same time, there is an urgent need to identify molecular targets involved in breast cancer carcinogenesis and drug resistance, and to develop selective drug delivery systems with optimal physicochemical characteristics that can simultaneously circumvent drug resistance and confer molecular targeting. However, despite the progress achieved to date in these areas, there is still a compelling requirement for deeper and more comprehensive understanding of the mechanisms involved in chemoresistance, and the interactions between polymer nanoparticles (PNPs) and cells at the molecular level, since the conventional cytotoxicity biochemical can measure cell metabolic activity as a proxy of cell-viability. Therefore, the information that can be derived from single end-point assays will fall short of providing a comprehensive depiction of complete biological responses or emphasising the impacted biochemical pathways following any exposure to treatments/materials. To address these challenges, new advanced tools such as the emerging metabolomics approaches are being recently employed to study nanomedicine related biological responses at the molecular level.